2014
DOI: 10.5152/jtgga.2014.14206
|View full text |Cite
|
Sign up to set email alerts
|

A new biological marker candidate in female reproductive system diseases: Matrix metalloproteinase with thrombospondin motifs (ADAMTS)

Abstract: Review 250Introduction A Disintegrin-like and Metalloproteinase with Thrombospondin type-1 motif (ADAMTS) proteinases, which are released outside the cell (soluble), have very critical roles in damage and repair of extracellular matrix (ECM) processes (remodeling) (1). The ADAMTS family, which degrades ECM structural substrates, such as collagen, aggrecan and versican, has 19 family members (2). These enzymes, which are associated with a great deal of vital physiological processes in the ECM, are inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 56 publications
1
25
0
1
Order By: Relevance
“…Previous studies have shown that the ADAMTS family plays an essential role in regulating the menstrual cycle, ovulation, implantation and maintaining pregnancy . Alterations in the extracellular matrix and abnormal placentation are considered leading causes of GDM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the ADAMTS family plays an essential role in regulating the menstrual cycle, ovulation, implantation and maintaining pregnancy . Alterations in the extracellular matrix and abnormal placentation are considered leading causes of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the ADAMTS family plays an essential role in regulating the menstrual cycle, ovulation, implantation and maintaining pregnancy. 8 Alterations in the extracellular matrix and abnormal placentation are considered leading causes of GDM. Changes in the structure, function and expression of ADAMTS proteins and proteoglycans have been observed in the extracellular matrix of fetal membranes of pregnant women with GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic activities of these proteases are inhibited by tissue inhibitor of metalloproteinase-3 (TIMP-3) (12). ADAMTSs play a critical role in the remodeling of ECM as well as many other physiological processes, including embryonic development, cell migration, and angiogenesis (13,14). ADAMTS family members have been implicated in the pathologies of many diseases, including cancer, inflammatory conditions, especially arthritic diseases, and atherosclerosis (14).…”
Section: Introductionmentioning
confidence: 99%
“…ADAMTSs play a critical role in the remodeling of ECM as well as many other physiological processes, including embryonic development, cell migration, and angiogenesis (13,14). ADAMTS family members have been implicated in the pathologies of many diseases, including cancer, inflammatory conditions, especially arthritic diseases, and atherosclerosis (14). A limited number of studies have shown the expression pattern of some ADAMTS subtypes in human placenta and their possible implication in gestational trophoblastic diseases (15,16); however, a more comprehensive study is required to show the expression pattern of all ADAMTS family members in preeclamptic placentas.…”
Section: Introductionmentioning
confidence: 99%
“…A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS) proteases are a group of secreted proteases that contains 19 members in humans (11). These proteins perform important tasks in the protection of the structure and function of cells in humans, particularly in the turnover and remodeling of the ECM.…”
Section: Introductionmentioning
confidence: 99%